If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3+4(2x-6)=15
We move all terms to the left:
3+4(2x-6)-(15)=0
We add all the numbers together, and all the variables
4(2x-6)-12=0
We multiply parentheses
8x-24-12=0
We add all the numbers together, and all the variables
8x-36=0
We move all terms containing x to the left, all other terms to the right
8x=36
x=36/8
x=4+1/2
| 16x+5x-2=4-5x | | -108=-4k3 | | p+4=3p-6 | | 3n+4=5 | | -7+5+3x=1 | | 29x-40=4x+6 | | 36n2=576 | | 24-8p=-24 | | 1/9+x=1/8 | | 3x(x-2)=30 | | u/13=11/3u= | | Y=19.95x+20 | | g/4-1=-6 | | 3x+(2x+5)=10x+15 | | 3x+(2x+5)=10x+115 | | 4(x-4)=2x+8 | | 3(x+1)=2(x+5 | | 6x-x=14 | | 207=70-w | | 5-6y=19y+10 | | 8(n-89)=8 | | 8=p/5-54 | | 3x-5=48 | | 6x+2=14=X+3 | | 53=4+7y | | 2(5x=3)=6x-3 | | 5^-6x=125^3-x | | -7d+1=-34 | | c+2/45=85/5 | | 3(z-9)=30 | | -3(2n-3)=25-8n+14 | | 2/5n=3/5n+2 |